Geomechanical effects of co2 storage in geological structures: two case studies - Soltanzadeh, M.; Hakim, SJS; Ibrahim, MHW.; Shahidan, S.; Mokhatar, SN.; Lim, AJMS (International Journal of Engineering and Technology, 2022)
Storage of CO2 in subsurface can assist to mitigate CO2 emission without extensively interfering with industrial activity and development. The main reason for geological storage to trap CO2 underground for a long time. However, the injection of CO2 may compromise the sealing characteristics of the caprock and, consequently, the containment of the underground CO2 storage unit as well. For instance, the injection of CO2 into a reservoir resulted in pore pressure and temperature changes leading to deformation and stress changes in the injection target and the rocks that surround it. These changes can influence the hydraulic integrity of the geological storage. The potential hazards could then impose different environmental, health, safety, and economic risks. Therefore, the geomechanical assessment of caprock integrity is critical for the storage of carbon dioxide. This research reviewed two different cases of underground CO2 storage in Canada and the workflows used for the assessment of geomechanical effects of CO2 injection on caprock integrity. It reviewed the processes of data collection, geomechanical characterization, and fluid flow modeling. These reviews highlighted the significance of geomechanical characterization and the fact that it is faced with significance challenges that could be addressed by data integration and geostatistical analysis. These reviewed studies implemented both analytical and numerical geomechanical models. While analytical models seem to be great choices for preliminary geomechanical analysis, numerical models are also necessary for a more detailed analysis.Â Â